2005
DOI: 10.1111/j.1532-5415.2005.53553.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dementia Cases in the Community: A Brazilian Experience

Abstract: This simple method was appropriate to identify cases of dementia in the general population and can possibly be extended to other developing countries with limited resources to be applied in health programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 20 publications
4
56
0
6
Order By: Relevance
“…†prevalence in the 90 years or over age group. Data from the Uruguay study (Ketzoian et al, 1997) and one Brazilian study (Ramos-Cerqueira et al, 2005) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…†prevalence in the 90 years or over age group. Data from the Uruguay study (Ketzoian et al, 1997) and one Brazilian study (Ramos-Cerqueira et al, 2005) …”
Section: Resultsmentioning
confidence: 99%
“…Studies carried out in five LA countries were identified in the databases, namely, Brazil (Herrera et al, 2002;Ramos-Cerqueira et al, 2005;Bottino et al, 2008), Colombia (Pradilla et al, 2003;Diaz-Cabezas et al, 2006), Cuba (Llibre et al, 1999;2005), Uruguay (Ketzoian et al, 1997) and Venezuela (Maestre et al, 2002;Molero et al, 2007). One Chilean (Albala et al, 1997) and one Peruvian (Custodio et al, 2007) study, presented as abstracts, were also identified.…”
Section: Resultsmentioning
confidence: 99%
“…Walking thus appears as a parameter to maintain as long as possible in these patients. Motor dysfunction in Alzheimer's disease is a late symptom and may appear in the form of extrapyramidal signs and abnormal gait, resulting in immobilization (Bottin et al, 2002;Ramos et al, 2005). The motor changes can manifest themselves in many different forms and stages of Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Major brain disorders as well as central nervous or cognitive failure, have common signs they share each other [1][2][3]. It is remains important to evaluate precisely without or before invasive investigations, which profile the disease hides behind the symptoms in front.…”
Section: Introductionmentioning
confidence: 99%